Showing off Your Social Capital: Homophily of Professional Reputation and Gender in Journalistic Networks on Twitter. Issue 4 (4th May 2021) - Maares, Phoebe; Lind, Fabienne; Greussing, Esther
Abstract: Social media like Twitter have become critical tools for public discourse and journalistic practice as they are assumed to enable equal conversations and engagement between different societal actors. However, recent studies have found that Twitter reproduces existing networks and hierarchies, indicated through homophily where dominant journalistic users with high symbolic capital tend to amplify and engage more with colleagues of similar symbolic status, which legitimizes their authority and dominance in the public sphere. Still, an in-depth understanding of how this manifests and might be rectified is lacking. To fill this gap, we explore the tweeting behaviour of 356 journalists in Austria, as social capital and personal networks are especially relevant to be recognized by peers. Our findings show strong homophilous tweeting behaviour for those with high professional reputation and for men. New entrants aim more towards gaining visibility in these tight-knit groups.